Redox-responsive hyaluronan-conjugated polypyrrole nanoparticles targeting chemo-photothermal therapy for breast cancer - Sun, Jingjun; Zhu, Shuangjiu; Xu, Weixuan; Jiang, Guoqin (Frontiers in Bioengineering and Biotechnology, 2022)
The combination of chemo-photothermal therapy has a wide application prospect in the intensive treatment of cancer. In this study, we developed a complex nanoparticle consist of polypyrrole, cystine dihydrochloride and hyaluronan. The paclitaxel drug loaded polypyrrole based complex nanoparticles exhibited good photothermal effects, and the drug release would be triggered by multi-model response of temperature and redox. In vitro biological studies indicated the nanoparticles could effectively induced apoptosis of MDA-MB-231 breast cancer cells involved in the potential mechanism of inhibition of biological expression of heat shock proteins and JAK-STAT signaling pathway. In addition, the nanoparticles have a significant inhibitory effect on cancer growth in breast tumor-bearing mice model, indicating that they have great potential for synergistic chemo-photothermal therapy.